PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP HARGA SAHAM PERIODE 2019-2021 (Studi Empiris Perusahaan Sub Sektor Makanan dan Minuman yang Tercatat di BEI) - Erlian Dandy N.B.; Endang Winarsih; Santosa Tri Prabawa (JURNAL WIRANOMIKA, 2024)
Abstract: Economic growth in Indonesia is influenced by various things, one of which is the capital market. The capital market is part of the financial market and a meeting place for investors and companies that have gone public. The Indonesian economy greatly influences the price of shares in circulation. This research aims to determine the influence of capital structure, company size and profitability on share prices in food and beverage companies listed on the IDX for the 2019-2021 period. This type of research is qualitative which is used to examine a predetermined population or sample. In this research, samples were taken using a purposive sampling technique based on the determined characteristics of 21 food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2019 period. The analysis techniques used are descriptive statistics, classical assumption test, multiple linear regression analysis, t test, F test, R test. research shows partial calculations that capital structure has a significant value (0.007 ≤ 0.05), meaning that capital structure influences share prices, company size has a significant value (0.000 ≤ 0.05), meaning that company size influences share prices, profitability has a significant value (0.367 ≥ 0.05), meaning that profitability has no effect on share prices. Meanwhile, the results of the simultaneous test show that together the capital structure, company size and profitability variables have a significant value of (0.000 ≤ 0.05), which means they have an influence on stock prices in Indonesia. Keywords : Capital Structure, Company Size, Profitability and Share Price